NEW MICROPALAEONTOLOGICAL EVIDENCE FOR A LATE TRIASSIC SHAN-THAI OROGENY - Ishida K.; Nanba A.; Hirsch F.; Kozai T.; Meesook A. (My University, 2006)
The Shan-Thai block is viewed as a remnant of Paleotethys in South East Asia. The general consensus about its origin is that it happened through the rifting from Gondwanaland and final amalgamation to Eurasia, sealed by fluvial-shallow marine Jurassic deposits. As the main Paleotethyan closure, the Nan-Uttaradit/Nan-Chantaburi and Bentong-Raub sutures were proposed by other workers. However, a suture further west, flanked by the Gondwana-Tethys divide (GTD), is advocated here as the main Paleotethyan closure. The Middle and Late Triassic radiolarian faunas were extracted from a chert-sequence in the Mae-Sot and Umphang areas of NW Thailand. The radiolarian faunas indicate early Ladinian, early-middle Norian, and Norian-Rhaetian, individually. The Triassic chert-sequence is overlain by the ‘Jurassic base-conglomerate’. The limestone and chert clasts in the conglomerate yield Early-Late Triassic conodonts and Middle-Late Triassic radiolarians, respectively. Chert clasts in the conglomerate yield among others Norian-Rhaetian radiolarians that are correlative with those from TM3, while Early-Late Triassic conodonts are found in limestone clasts. The silici-pelagic origin of the clasts suggests the Mae Sariang Zone that amalgamated the parts of the Shan-Thai block. This first finding of Late Triassic radiolarians from chert-sequence, next to the Middle Triassic and older radiolarian faunas, adds another element to the reconstruction of the sequence now comprised in the Mae Sariang Zone, west of the Nan-Uttaradit Suture. The occurrence of Triassic limestone, as that of the Chaiburi Formation in the Mae Sariang Zone, or the Kodiang Limestone in the “Western Zone”, may elucidate the question about the provenance of the Triassic conodont-bearing limestone clasts in the Jurassic base-conglomerate that seals the Mae-Sariang Zone. The newly dated Triassic sequence is further sealed by the continental-shelf deposits of the Toarcian-early Bajocian Hua Fai Group.
Keywords: RADIOLARIAN CHERT; CONODONT LIMESTONE; PROVENANCE; SHAN-THAI TERRANE; END-TRIASSIC OROGENY; Bajocian; Toarcian; Rhaetian; Norian; Ladinian; Mesozoic::Jurassic::Middle::Bajocian; Мезозой::Юрская::Средний::Байосский; Mesozoic::Jurassic::Lower::Toarcian; Мезозой::Юрская::Нижний::Тоарский; Mesozoic::Triassic::Upper::Rhaetian; Мезозой::Триасовая::Верхний::Рэтский; Mesozoic::Triassic::Upper::Norian; Мезозой::Триасовая::Верхний::Норийский; Mesozoic::Triassic::Middle::Ladinian; Мезозой::Триасовая::Средний::Ладинский